2005
DOI: 10.1207/s15328015tlm1703_13
|View full text |Cite
|
Sign up to set email alerts
|

Internists Training Medical Residents in Pelvic Examination: Impact of an Educational Program

Abstract: This program, in which internists trained medical residents in pelvic examination, utilized real patients, improved participants self-assessed competency, and may increase the likelihood of residents performing pelvic examination in primary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
6
0
1
Order By: Relevance
“…Some studies showed improvement in learners’ clinical skills performance as a result of training by patients. This improvement was measured through objective structured clinical examination (OSCE) scores, 14,16,28,46,55 assessment by teaching associates (such as GTAs), 18,56 skills assessment after teaching, 20,24–26,29,37,50,62,65,68,69 self‐assessment, 6,7,57,61,62 and increased ability to palpate anatomical structures (ovary, breast) or pathology (breast lumps) 35,39,43,60,71 . One study 32 reported improved clinical performance after mental exercise to recall the steps of gynaecological examination.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies showed improvement in learners’ clinical skills performance as a result of training by patients. This improvement was measured through objective structured clinical examination (OSCE) scores, 14,16,28,46,55 assessment by teaching associates (such as GTAs), 18,56 skills assessment after teaching, 20,24–26,29,37,50,62,65,68,69 self‐assessment, 6,7,57,61,62 and increased ability to palpate anatomical structures (ovary, breast) or pathology (breast lumps) 35,39,43,60,71 . One study 32 reported improved clinical performance after mental exercise to recall the steps of gynaecological examination.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of articles described interventions amongst undergraduate medical students 3,5–8,14–55 . The remainder described outcomes amongst postgraduate trainees, 56–63 practising clinicians, 64–69 other health professionals 70 and other groups 71–73 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This scale has been used successfully in a number of other medical education studies investigating CPD and training. Goldstein et al (2005) used a 5-point Likert scale to evaluate an educational programme on pelvic examination for 1st year medical residents. They used the scale pre-and post-training to determine changes in attitude and competency.…”
Section: Discussionmentioning
confidence: 99%
“…Survey questions were adapted from prior surveys used in studies focused on teaching IM residents and internists about women's health. 3,4…”
Section: Methodsmentioning
confidence: 99%